1976
DOI: 10.1083/jcb.69.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the flagellar apparatus and associate cytoplasmic microtubules in the quadriflagellate alga Polytomella agilis.

Abstract: The organization of microtubular systems in the quadriflagellate unicell Polytomella agilis has been reconstructed by electron microscopy of serial sections, and the overall arrangement confirmed by immunofluorescent staining using antiserum directed against chick brain tubulin. The basal bodies of the four flagella are shown to be linked in two pairs by short fibers. Light microscopy of swimming cells indicates that the flagella beat in two synchronous pairs, with each pair exhibiting a breast stroke-like mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…In the light of this situation algae with equally numbered cruciate root systems (Urospora: Kristiansen, 1974; Carteria: Lembi, 1975; Schizorneris: Birkbeck et al, 1974) appear to be quite distinct from algae posessing the X-2-X-2 type of root system. It is however suggested that these algae should be reinvestigated using serial sections and methods to distinguish between root microtubules and secondary cytoskeletal microtubules, because the latter especially in quadriflageilate cells seem to be organized at electron-dense material adjacent to root microtubules (e. g. Brown et al, 1976) and can be mistaken for root microtubules. Since the two types of microtubules show different sensitivity to cold and microtubule inhibitors (Melkonian et al, in preparation) a reevaluation might be profitable.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the light of this situation algae with equally numbered cruciate root systems (Urospora: Kristiansen, 1974; Carteria: Lembi, 1975; Schizorneris: Birkbeck et al, 1974) appear to be quite distinct from algae posessing the X-2-X-2 type of root system. It is however suggested that these algae should be reinvestigated using serial sections and methods to distinguish between root microtubules and secondary cytoskeletal microtubules, because the latter especially in quadriflageilate cells seem to be organized at electron-dense material adjacent to root microtubules (e. g. Brown et al, 1976) and can be mistaken for root microtubules. Since the two types of microtubules show different sensitivity to cold and microtubule inhibitors (Melkonian et al, in preparation) a reevaluation might be profitable.…”
Section: Discussionmentioning
confidence: 98%
“…With this technique Hyams & Chasey (1974) have shown the presence of 4 very short striated fibres (periodicity 25-30 nm) associated with the four microtubular roots in Dunaliella. The only quadriflagellate organism in which striated fibres overlying twostranded roots were found is Polytomella (Brown et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…In these organisms, the centriole-basal-body complex is strategically positioned with an associated, highly defined set of microtubule rootlets and/or sets of striated filament appendages. These microtubules and microfilament appendages have defined positions, polarities and orientations that assist in defining overall shape and form (Brown et al, 1976;Hibberd, 1975;Holmes and Dutcher, 1989). Therefore, it is impossible to separate our understanding of the duplication and segregation of centrosomes and basal bodies from the wider implications for cell morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The plastid of Polytomella spp., which derives from a primary endosymbiosis, has been characterized by ultrastructural studies and typically contains copious amounts of starch (Moore et al, 1970;Brown et al, 1976). However, experiments searching for evidence of a plastid gene expression system within it have proven unsuccessful (Nedelcu et al, 1996;Nedelcu, 2001).…”
mentioning
confidence: 99%